Diagnostic Dilemma in Endocervical Adenocarcinoma– A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Adenocarcinoma of endometrium and uterine cervix may demonstrate significant morphological overlap. The distinction between these two entities prior to surgical resection is clinically significant as assigning the primary site dictates treatment and prognosis. The diagnostic dilemma is approached by a panel application of immunohistochemical stains, traditionally composed of CEA, Vimentin, ER, PR, p16. Most cases are successfully managed by this panel, however, in difficult cases additional tools may needed to suggest a more definitive diagnosis. But in respect to our country, considering the socioeconomic condition and affordability as well as availability it may not be always possible to apply additional tools, that’s why traditional panel is usually applied in diagnosis.Bangladesh J Obstet Gynaecol, 2025; Vol. 40(2): 122-125